Fabrication of a Bare Optical Fiber-Based Biosensor - Zhang, Yu-Jun (Micromachines (Basel), 2019)
A bare optical fiber-based biosensor is proposed for measuring the refractive index of different liquids and the binding kinetics of biomolecules to the sensor surface. This optical fiber sensor is based on the Kretschmann’s configuration to attain total internal reflection (TIR) for surface plasmon resonance (SPR) excitation. One end of the bare optical fiber is coated with a gold film. By guiding the light source from the other end into the optical fiber, the light is reflected from the gold-deposited end and the surface evanescent wave is excited in the gold film-transparent material interface. Methanol and ethanol solutions with different refractive indices are used for measuring the corresponding changes in the peak values of the spectra and calculating the corresponding sensitivities. These values are experimentally determined to be in the order of 10(−4)~10(−5) refractive index unit (RIU). Binding of proteins onto the sensor surface is also monitored in real time to obtain the binding kinetics. We believe that, in the future, this optical fiber sensor can serve as a useful biosensor for in situ measurement of allergens, antibody–antigen interactions, and even circulating tumor cells in the blood.